The Role of Cytokines in the Fibrotic Responses in Crohn’s Disease - Curciarello, Renata; Docena, Guillermo H.; MacDonald, Thomas T. (Frontiers in Medicine, 2017)
Crohn's disease (CD) is an idiopathic disorder of the gut thought to be caused by a combination of environmental and genetic factors in susceptible individuals. It is characterised by chronic transmural inflammation of the terminal ileum and colon, with typical transmural lesions. Complications, including fibrosis, mean that between 40% and 70% of patients require surgery in the first 10 years after diagnosis. Presently, there is no evidence that the current therapies which dampen inflammation modulate or reverse intestinal fibrosis. In this review we focus on the cytokines which may lead to fibrosis and stenosis, and the contribution of experimental models to the understanding and treatment of gut fibrosis.